Macrostylis cerritus sp. nov., a new species of Macrostylidae (Isopoda: Asellota) from the Weddell Sea, Southern Ocean - Vey, Aidan; Brix, Saskia (Zootaxa, 2009)
Macrostylis cerritus sp. nov. (Macrostylidae) is described from the Weddell Sea, Antarctica, at a depth of 2149 m. The new species differs from other species of Macrostylis due to the incisor with 4 cusps; the strongly hook-shaped ischium of pereopod 3; pereopod 4 being greatly reduced and juvenile in appearance; the operculum bearing a ventral spine-like seta; and the absence of pleopod 5. This species is the fourth deep-sea macrostylid identified from the Southern Ocean, and is one more species described from the specimens of ANDEEP I–III expeditions.